Enhanced spin-orbit torque in Ni81Fe19/Pt bilayer with NdNiO3 contact - Seyeop Jeong; Jongmin Lee; Soogil Lee; Jungmin Park; Donghyeon Lee; Jimin Jeong; Heechan Jang; Eunkang Park; Younghun Jo; Nyun Jong Lee; Kyoung-Whan Kim; Byong-Guk Park; et al. (American Institute of Physics Inc., 2021)
Spin orbit torque (SOT) is essential to magnetization modulation in various ferromagnet/non-magnet bilayers. In this study, we demonstrated that SOT can be enhanced in a hybrid system composed of a perovskite oxide NdNiO3 (NNO) and a Ni81Fe19/Pt bilayer. We also find that the SOT enhancement might be attributed to spin absorption at the interface between the NNO and Ni81Fe19 layers. Our findings suggest that metal-oxide hybrid structures can be promising systems for the development of efficient spin-orbitronic devices.